Formulation and Quality Evaluation of Instant Sweet-Shrimp Paste (Kapi Wan) Powder - Phanumong, Putkrong; Kraboun, Kitisart; Pangsaard, Jitchanok; Polanan, Tipparat; Promwong, Sujintorn; Tantivitittapong, Ithinath; Chowvanayotin, Pornrak (Journal of Food Health and Bioenvironmental Science, 2023)
The sweet-shrimp paste sauce (Kapi Wan) is a traditional Thai fruit dip prevalent in Southeast Asia. In this study, an instant sweet-shrimp paste powder was developed as a new product for convenience, portability and ease to use. The shrimp paste powder prepared by sun drying in a combination of hot air oven exhibited a low moisture content (8.53%) and aw value (0.47) which preserved the character of natural color and flavor of the raw material. For an instant product preparation, the proportion of three ingredients, e.g., shrimp-paste powder (40-60%), palm sugar powder (10-30%) and cayenne pepper (10-30%), mixed with 30% ground dried shrimp (fixed ingredient) were studied. Choosing the most suitable formula from a total of 7 treatments based on the sensory attributes in terms of appearance, color, flavor, taste and overall liking by using the overlapping area of the contour plot of all factors. The best formula was treatment No. 1 (46.15% shrimp paste powder, 23.08% palm sugar powder, 7.69% cayenne pepper and 23.07% ground dried shrimp) which had the highest score in taste and overall liking. The product contained 12.01% of moisture content and the aw value was 0.52. Total protein, fat, carbohydrate and ash contents were 33.52, 3.81, 31.49 and 19.01%, respectively. The second best treatment was Treatment No. 5 (41.03% shrimp paste powder, 17.95% palm sugar powder, 17.95% cayenne pepper and 23.07% ground dried shrimp), which showed similar physiochemical properties, except a significantly (p≤0.05) higher in fat (4.87%) and lower in ash (18.37%) content. Both treatments had the potential to develop an instant sweet-shrimp paste powder; as treatment No. 1 being a non-spicy and spicy formula as treatment No. 5. The sensory score ranged from like slightly to like moderately.